Biosensors nanomaterials, approaches, and performance-enhancement strategies - Kaur, Baljinder; Kumar, Santosh; Kaushik, Brajesh Kumar (IEEE Press Series on sensors, 2025)
Comprehensive resource covering new technologies, materials, strategies, and recent advancements in the field of biosensing Biosensors summarizes cutting-edge technologies in biosensing, including gene editing (known as Clustered Regularly Interspaced Short Palindromic Repeat or CRISPR), quorum sensing utilizing inter and intra cell signals, two-dimensional (2D) materials and aptamer-mediated sensor designs, and more, with additional coverage of the latest materials, strategies, and advancements made in the field. Chapters are categorized on the basis of various bio-recognition elements that include aptamer, nucleic acid, enzymes, antibodies, bacteriophages, peptides, and molecular imprinted polymers. Plasmonic, surface-enhanced Raman scattering, colorimetric, fluorescence, electrochemical, magneto and piezo-electric biosensor sensing techniques are also considered.